PEMANFAATAN MULTIMEDIA DALAM PENGENALAN BILANGAN PADA USIA 5-6 TAHUN DI TK TUNAS HARAPAN - Indri Wulandari; Marmawi R; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2022)
This research is motivated by problems regarding children aged 5-6 years at Tunas Harapan Kindergarten, Singkawang City where the children who are the subjects of this research are some children who do not know numbers, and cannot count and match numbers with number symbols. Researchers feel that interesting learning media can help children. This study aims to determine the use of multimedia in number recognition in children aged 5-6 years at Tunas Harapan Kindergarten, Singkawang City. This researchis a qualitative descriptive research with the subject of this research are teachers and children in group B1 totaling 15 people. The conclusions of this study are: The use of multimedia in mentioning number symbols shows that most of the 13 children have developed as expected, but a small portion of 2 children are still slow to reverse in mentioning number symbols, The use of multimedia in counting 1-10 as a large 13children can already develop as expected, but after being tried individually, it is known that a small part of 2 children cannot count sequentially, the use of multimedia in matching numbers 1-10 most of the 13 children have been able to match numbers with number symbols correctly but a small part of 2 children need to be guided by the teacher and Children's learning outcomes in number recognition by utilizing multimedia used by teachers have developed as expected.